Alternative Dispute Resolution in SMEs in the Construction Industry in Masvingo Urban, Zimbabwe - Herbert Tavengahama, Tafara; Mashavira, Nhamo; Nyanga, Takupiwa; Ernest Muchadenyika, Chakanaka (Ushus Journal of Business Management, 2020)
Dispute handling may present particular problems for SMEs. The research explored the Alternative Dispute Resolution (ADR) methods used in SMEs and their implications on the performance of SMEs in the construction industry in Zimbabwe. The study revealed that collective bargaining and negotiation are the main ADR methods used in the SMEs while conciliation and arbitration are utilized externally at NEC and the ministry of labour. It was also noted that most SMEs do not have established ADR structures and collective bargaining and negotiation had an impact on employee performance. Collective Bargaining, Conciliation and Adjudication